2022
DOI: 10.1155/2022/1503227
|View full text |Cite
|
Sign up to set email alerts
|

Early Change in Platelet Count and MPV Levels of Patients Who Received Hemodialysis for the First Time: Mogadishu Somalia Experience

Abstract: Introduction. Mean platelet volume (MPV) is a marker used to assess the platelet’ size and is also an indicator of platelet reactivity and prothrombotic status. Objective. In this study, we aimed to determine the relationship between MPV and biochemical parameters in patients who had received hemodialysis (HD) for the first time and then in respect of those same patients after their fourth HD. Method. 151 HD patients were enrolled in this study. Patients were eligible for inclusion if they had received their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“… 34 Therefore, it is of great clinical significance to identify simple, inexpensive, and effective predictors to identify high-risk AIS in hemodialysis patients and to take preventive measures. MPV in hemodialysis patients is affected by many factors, such as the inflammatory response 35 and EPO application, 36 and is related to the occurrence of thrombosis-related diseases. 17 , 21 However, there are no relevant reports on the predictive value of MPR for AIS.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Therefore, it is of great clinical significance to identify simple, inexpensive, and effective predictors to identify high-risk AIS in hemodialysis patients and to take preventive measures. MPV in hemodialysis patients is affected by many factors, such as the inflammatory response 35 and EPO application, 36 and is related to the occurrence of thrombosis-related diseases. 17 , 21 However, there are no relevant reports on the predictive value of MPR for AIS.…”
Section: Discussionmentioning
confidence: 99%
“…During platelet activation, active substances are released from alpha-granules, which additionally intensify their activation [ 4 ]. The mean platelet volume (MPV) is a well-established marker of platelet activation [ 5 , 7 ]. Research has revealed elevated MPV values among individuals with type 2 diabetes [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%